Pengembangan Sirkuit Bongkar Pasang untuk Aktivitas Fisik Motorik Kasar di Lembaga Prasekolah dengan Lahan Minimalis - Ari Kusuma Sulyandari; Mutiara Sari Dewi (SELING: Jurnal Program Studi PGRA, 2020)
Development of research to stimulated gross motor physical development. On minimalist land. With a circuit that had several posts. In order to be a minimalist land solution. Easy to do, fun and not dangerous for children. From the results of a pre-observational study in preschool Permata Hati. Gross motor physical learned used circuits in the classroom has never been implemented and needs to be implemented. This research used by Borg and Gall, simplified into just seven steps. Data collection techniques used observation, interviews and questionnaires. The results of the development of expert test results on product has tested in small groups and large groups. Small group trial used a sample of 6 children. Large group trials used 35 children. The final of observation result shows that 89.5% of this learning makes it easy for children, 100% fun and 100% safe circuits to used for children. The result has development of gross motor physical learned has feasible to used.